2006
DOI: 10.1111/j.1365-2516.2006.01314.x
|View full text |Cite
|
Sign up to set email alerts
|

The obstetric and gynaecological management of women with inherited bleeding disorders – review with guidelines produced by a taskforce of UK Haemophilia Centre Doctors’ Organization

Abstract: Summary. The gynaecological and obstetric management of women with inherited coagulation disorders requires close collaboration between obstetrician/ gynaecologists and haematologists. Ideally these women should be managed in a joint disciplinary clinic where expertise and facilities are available to provide comprehensive assessment of the bleeding disorder and a combined plan of management. The haematologist should arrange and interpret laboratory tests and make provision for appropriate replacement therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
307
0
34

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(345 citation statements)
references
References 264 publications
(367 reference statements)
4
307
0
34
Order By: Relevance
“…Even if somewhat non-specific (anaemia, pallor and apnea) and sometimes more unambiguous (seizures, lethargy and paresis), these recurrent symptoms must be recognized by caregivers in maternity hospitals as possibly because of ICH [12,33,39]. In the absence of high level evidence-based guidelines, questions such as the role of ultrasound scan (screening or targeted imaging) and the treatment approach (prophylactic or early curative), have been discussed and remain under debate [11,16,33,40]. The role of imaging should be considered along with the optimal timing of discharge from hospital, because it has been observed that ICH occur rather early (mean 4-5 days) [12].…”
Section: Prevention and Treatment Of Neonatal Ichmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if somewhat non-specific (anaemia, pallor and apnea) and sometimes more unambiguous (seizures, lethargy and paresis), these recurrent symptoms must be recognized by caregivers in maternity hospitals as possibly because of ICH [12,33,39]. In the absence of high level evidence-based guidelines, questions such as the role of ultrasound scan (screening or targeted imaging) and the treatment approach (prophylactic or early curative), have been discussed and remain under debate [11,16,33,40]. The role of imaging should be considered along with the optimal timing of discharge from hospital, because it has been observed that ICH occur rather early (mean 4-5 days) [12].…”
Section: Prevention and Treatment Of Neonatal Ichmentioning
confidence: 99%
“…Even if some guidelines for haemophilia care include recommendations for the management of carrier women and the mode of delivery, successful prevention of ICH in newborns with haemophilia remains as a well-documented difficult task [40]. Actually, in identified carriers, prevention requires careful management and surveillance of the newborn, which means that the haemophilia specialist should transmit detailed information to obstetricians, anaesthesiologists and paediatricians in a multidisciplinary approach.…”
Section: Prevention and Treatment Of Neonatal Ichmentioning
confidence: 99%
“…32 The validity of PBAC has been questioned because of a wide variation in its specificity and sensitivity for diagnosis of menorrhagia in different studies. 18,[33][34][35] However, it is a simple non-invasive tool that can be helpful in clinical practice for the initial assessment and monitoring of treatment.…”
Section: Menorrhagia and Ibdsmentioning
confidence: 99%
“…There is no apparent increased bleeding risk for neonates with VWD, but for fetuses at risk of type 2 and 3 VWD invasive monitoring techniques or vacuum extraction and forceps use at delivery should be preferably avoided. 68 Prenatal diagnosis is required only in selected families with type 3 VWD.…”
Section: Casementioning
confidence: 99%